1989
DOI: 10.1042/bj2580645
|View full text |Cite
|
Sign up to set email alerts
|

T-cell recognition and antigen presentation of myoglobin. Protein recognition by site-specific T-cell clones is influenced by amino acid substitutions outside the site

Abstract: Six T-cell clones from SJL mice were prepared from T-cell lines that were obtained by passage with synthetic myoglobin (Mb) peptide 107-120. In addition, a T-cell clone, specific to this region of Mb, was isolated from a Mb-passaged T-cell culture. The proliferative responses of these clones to Mb variants from 14 different species were studied. It was found, as expected, that amino acid replacements within the site affected its recognition by the T-cell clones. In addition to these effects, the T-cell recogni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

1989
1989
1998
1998

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…The results reported here show that LNCs whose specificity is directed against a region [a- (31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)] that is completely buried within the subunit association surfaces in Hb recognize the free synthetic peptide and the isolated subunit but not the intact tetramer. LNCs against regions that are only partially involved in subunit association or against exposed regions that are not involved at all in subunit contacts recognize the peptide and the isolated subunit as well as intact Hb.…”
Section: Resultsmentioning
confidence: 85%
See 4 more Smart Citations
“…The results reported here show that LNCs whose specificity is directed against a region [a- (31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)] that is completely buried within the subunit association surfaces in Hb recognize the free synthetic peptide and the isolated subunit but not the intact tetramer. LNCs against regions that are only partially involved in subunit association or against exposed regions that are not involved at all in subunit contacts recognize the peptide and the isolated subunit as well as intact Hb.…”
Section: Resultsmentioning
confidence: 85%
“…It has been shown that site-specific T-cell recognition of myoglobin is influenced by amino acid substitutions outside of the site itself (41,42). These substitutions were distant in sequence from the site but close to it in the 3-dimensional structure.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations